2022
DOI: 10.3390/genes13071250
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Hemorrhage Genetics

Abstract: Intracerebral hemorrhage (ICH) is a devastating type of stroke, frequently resulting in unfavorable functional outcomes. Up to 15% of stroke patients experience ICH and approximately half of those have a lethal outcome within a year. Considering the huge burden of ICH, timely prevention and optimized treatment strategies are particularly relevant. Nevertheless, ICH management options are quite limited, despite thorough research. More and more trials highlight the importance of the genetic component in the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Another possible explanation for our findings is that some subtypes of ischemic stroke present additional phenotypic dilemmas, such as the cardiogenic stroke subtype, whereas the phenotype of ICH is more uniform ( 71 ). Moreover, genetic factors are important in the pathogenesis of ICH ( 72 ). It is estimated that up to 44% of cases of ICH are heritable, and possessing an ICH first-degree relative increases the risk of developing the condition by a factor of six ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for our findings is that some subtypes of ischemic stroke present additional phenotypic dilemmas, such as the cardiogenic stroke subtype, whereas the phenotype of ICH is more uniform ( 71 ). Moreover, genetic factors are important in the pathogenesis of ICH ( 72 ). It is estimated that up to 44% of cases of ICH are heritable, and possessing an ICH first-degree relative increases the risk of developing the condition by a factor of six ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the relationship between genetic factors and the risk of hemorrhagic stroke. 16 Such as, angiotensin converting enzyme (ACE) I/D polymorphism may increase the risk of hemorrhagic stroke. 17 Polymorphism of ADH1B was related to the risk of hemorrhagic stroke in a Taiwanese population.…”
Section: Discussionmentioning
confidence: 99%
“…studies have shown that gene expression changes at the site of hemorrhage are focused on common genes and pathways. 14,22 Meanwhile, ICH's impact on molecular networks, including both pro-inflammatory and anti-inflammatory systems, offers insights into secondary injury mechanisms. 21,23 However, direct assessments of specific cell types in WMI models are still lacking.…”
Section: Despite the Clinical And Genetic Heterogeneity Of Ich Numerousmentioning
confidence: 99%
“… 9 , 10 The aftermath of hemorrhage includes activation of microglia cells, infiltration of inflammatory cells, and cytokine release, contributing to further WM injury (WMI). 11 , 12 These underlying processes present challenges for modeling and treatment, due to the condition's heterogeneity, 13 , 14 and a comprehensive understanding remains elusive.…”
Section: Introductionmentioning
confidence: 99%